Die Ausbeute der Kernreaktion Al27 (d, 2 p) Mg27 - Radicella, Renato; Rodríguez, J.; Baró, G. B. B.; Hittmair, Otto (Springer Berlin Heidelberg, 1958)
Fil: Radicella, Renato Comisión Nacional de Energía Atómica; Argentina